Strategi Pembelajaran PAI pada Kurikulum Merdeka Belajar di SMP Kreatif Aisyiyah Rejang Lebong - Zuhri Dwi Apriansah; Dewi Purnama Sari; Ngadri Yusro (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This study aims to analyze the implementation strategy of Islamic Religious Education Learning (PAI) at SMP Kreatif Aisyiyah in facing the challenges of the Society Era 5.0 in the context of the Independent Learning Curriculum. The research method used is qualitative with a case study model, collecting data through observation, interviews, and documentation. Data analysis is carried out by preparing, organizing, reading, and interpreting data in a qualitative narrative manner. The results showed that the PAI learning strategy at SMP Kreatif Aisyiyah adopts an interactive approach, integrating digital literacy, collaboration, and projects. This strategy uses technology and communication between students, and applies Islamic values in a real context, increasing Islamic understanding, digital skills, and cooperation. The stages of implementing this strategy include preparation, active learning, projects, and evaluation, with a holistic and student-centered approach. This approach enhances the relevance of Islamic values and students' readiness for the Era of Society 5.0. At SMP Kreatif Aisyiyah, students show a positive response to this strategy, with interactive methods and the use of technology that increases motivation, interest in learning, critical thinking, and collaboration. Students' character development includes tolerance, cooperation, integrity, and social ethics, which are important in preparing them for the Era of Society 5.0.